Brazilian Physical Education journals: Ethical and methodological aspects of publications with the elderly - Sandreschi P.F. (2018)
© 2018, Universidade Estadual de Maringa.The objective of the present study was to analyze ethical and methodological aspects involved in the publishing of studies with the elderly on Brazilian Physical Education journals. It is a narrative review that included national journals ranked as Qualis B1 or over and focused on the Physical Education field. From the seven journals selected, 191 articles were analyzed, which exclusively had senior citizens as participants. It was thus verified that most of the articles reported approval by the institution of origin's Research Ethics Committee and mentioned the Informed Consent Form; most studies used inquiry and testing as data collection techniques. In this way, it was concluded that, on Brazilian Physical Education journals, most published studies involving the elderly address the research's ethical aspects.